Gold Catalysis Meets Materials Science – A New Approach to π‐Extended Indolocarbazoles. Issue 2 (24th November 2020) - Hendrich, Christoph M.; Bongartz, Lukas M.; Hoffmann, Marvin T.; Zschieschang, Ute; Borchert, James W.; Sauter, Désirée; Krämer, Petra; Rominger, Frank; Mulks, Florian F.; Rudolph, Matthias; Dreuw, Andreas; Klauk, Hagen; et al.
Abstract: Herein we describe a modular, convergent synthesis of substituted benzo[ a ]benzo[6, 7]‐indolo[2, 3‐ h ]carbazoles (BBICZs) using a bidirectional gold‐catalyzed cyclization reaction as a key step. A building block strategy enabled the easy variation of substituents at different positions of the core structure and a general analysis of substitution effects on the materials properties of the target compounds. All BBICZs were fully characterized and their optical and electronic properties were studied experimentally as well as by computational methods. Organic thin‐film transistors based on eight selected derivatives were fabricated by vacuum deposition and charge‐carrier mobilities up to 1 cm 2 /Vs were measured. Abstract :